Anemia di Usia Sekolah: Tinjauan Pengetahuan, Sikap, dan Pola Makan pada Siswi SMPN 5 Banjarbaru 2024 - Ilmi, M. Bahrul; Anwary, Ahmad Zacky; Aquarista, M. Febriza; Annisa, Siti (Jurnal Akademika Baiturrahim Jambi, 2025)
The incidence of anemia at SMP Negeri 5 Banjarbaru is quite high according to the results of screening from the South Banjarbaru Health Center, with the number of students affected by anemia 57 students. This finding aims to find the relationship between knowledge, attitudes and diet with the incidence of anemia experienced by adolescent students of SMP Negeri 5 Banjarbaru. This finding is a quantitative study that is an analytical survey in a cross sectional approach using the Chi-Square Test. This study has a sample of 60 respondents using purposive sampling technique. The results of the bivariate analysis showed that knowledge had no relationship with the incidence of anemia (p-value = 0.836), there was no relationship between attitude and the incidence of anemia (p-value = 1.000), and there was a relationship between diet and the incidence of anemia (p-value = 0.033). Advice for schools to provide information about the impact of anemia regularly and independently regarding healthy eating knowledge to adolescent students, without waiting for the health authorities.